(untitled) (Itinera, 2019)
The first and fundamental experience as a theatre spectator usually happens during high school period. How do we make this first encounter as effective as possible? The project Acrobazie Critiche, supported by Fondazione Cariplo and targeting some high schools in Milan, aims to increase students’ awareness as spectators through their active participation and knowledge of dramatic theory. This paper examines premises, objectives and results of the project.